2018
DOI: 10.1177/0739456x18801057
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Resilience Planning: Alternative Pathways to Prepare for Climate Change

Abstract: Increasingly, local governments are creating resilience plans. What do these plans contain and how do they compare to other efforts to plan for climate change? We use plan evaluation to analyze 10 resilience plans from U.S. cities in the 100 Resilient Cites program and compare them to 44 climate change adaptation plans. Resilience plans lack critical elements to prepare cities for climate change but offer a platform to address economic, social, and environmental policies that may amplify climate change impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 35 publications
1
57
0
1
Order By: Relevance
“…It is however not possible to argue that it is mainstream urban policy, for reasons which will be discussed below. Further, as Woodruff et al have shown, adaptive policy making is increasingly being augmented by resilience planning, especially in the US [6]. Indeed, they argue that many municipalities may, in time, become more focused on resilience than adaptation, a point developed in the next section.…”
Section: Adaptationmentioning
confidence: 92%
See 2 more Smart Citations
“…It is however not possible to argue that it is mainstream urban policy, for reasons which will be discussed below. Further, as Woodruff et al have shown, adaptive policy making is increasingly being augmented by resilience planning, especially in the US [6]. Indeed, they argue that many municipalities may, in time, become more focused on resilience than adaptation, a point developed in the next section.…”
Section: Adaptationmentioning
confidence: 92%
“…In addition to the scrutiny that has been given to adaptation, we can also point to the body of literature devoted to resilience. While that could command a full length analysis, we can point to the work of Woodruff et al, who have assessed 44 adaptive plans in US cities and contrasted them with 10 resilience plans [6]. It is especially noteworthy that these J Sustain Res.…”
Section: Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Practitioners indicate that the capacity and support for action increases if an understanding of climate science and impacts is embedded directly into existing policies, plans, operations, and budget structures (Stults 2017;Woodruff et al 2019). Integrating climate-relevant science and policy into existing plans and structures (sometimes referred to as ''mainstreaming'') can enable practitioners to act in a timely fashion, identify overlaps with other sectors and stakeholders, and take advantage of funding from multiple sources.…”
Section: Practitioner Perspectives: How Assessed Knowledge Can Advancmentioning
confidence: 99%
“…This would move beyond the traditional "hard" paradigm of coast control or coastal protection to allow for more dynamic and socio-ecologically resilient alternatives, such as coastal accommodation and retreats based on natural protection against sea storms and rising sea levels. The fifth IPCC report and studies on needs for adaptation highlight the social, environmental, and economic benefits of no-regret strategies in climate change adaptation, which permit a low-cost reduction of risks under various climate change scenarios (Heltenberg, Siegel & Jorgensen, 2009;IPCC, 2014;Woodruff, Meerow, Stults & Wilkins, 2018;). Working with NBS as flexible and self-adjusting options is considered a key element of a no-regret strategy for coastal defence and adaptation (van Wesenbeeck et al, 2014), Some countries, such as the Netherlands, have historically incorporated natural protection measures (e.g., dune systems) as an essential part of coastal protection (van Koningsveld & Mulder, 2004).…”
Section: Introductionmentioning
confidence: 99%